2010
DOI: 10.1111/j.1467-9566.2010.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Volunteered, negotiated, enforced: family politics and the regulation of home smoking

Abstract: The protection of children from secondhand smoke in their homes remains a key objective for health agencies worldwide. While research has explored how parents can influence the introduction of home smoking restrictions, less attention has been paid to the role of wider familial and social networks as conduits for positive behaviour changes. In this article we explore how people living in Scotland have introduced various home smoking restrictions to reduce or eliminate children's exposure to tobacco smoke, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 50 publications
(52 reference statements)
0
60
0
Order By: Relevance
“…Even though families across all levels of deprivation have shown increased restrictions towards reducing SHS exposure in their homes, homes with greater disadvantage tend to have fewer restrictions 12. Mothers in disadvantaged communities tend to have more restricted lives and are therefore impacted less by tobacco control interventions aimed at the broader population 13. There is a clear and significant challenge to the public health community on how to deliver reductions in both frequency and intensity of children's exposure to SHS in these communities, but a lack of confidence by health professionals is raising this issue 14 15…”
Section: Introductionmentioning
confidence: 99%
“…Even though families across all levels of deprivation have shown increased restrictions towards reducing SHS exposure in their homes, homes with greater disadvantage tend to have fewer restrictions 12. Mothers in disadvantaged communities tend to have more restricted lives and are therefore impacted less by tobacco control interventions aimed at the broader population 13. There is a clear and significant challenge to the public health community on how to deliver reductions in both frequency and intensity of children's exposure to SHS in these communities, but a lack of confidence by health professionals is raising this issue 14 15…”
Section: Introductionmentioning
confidence: 99%
“…Parents/carers appear willing to hear messages around smoke-free families and SHS, particularly if these messages can offer information on support services (i.e. SFS) and are positioned as part of a wider range of initiatives designed to improve the health and home environment of the child [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence that parents and carers may be imposing smoking restrictions inside their homes and asking visiting smokers to smoke outside [20,21], these restrictions may relax as children grow older or to avoid compromising strong emotional and social ties [22,23]. Research literature points towards the importance of trying to encourage parents/carers to stop smoking, or at least to taking their smoking outside of the home away from their children, to reduce SHS exposure [24].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between participants' experiences of policies and SHS management are backed up by other qualitative studies that have identified different levels of tolerance, interaction styles, and power dynamics related to smoke exposure [53, 54], the implementation of home smoking policies [54], and reducing or quitting smoking during pregnancy [58]. Poland and colleagues identified heterogeneity in smokers and nonsmokers attitudes and responses to SHS.…”
Section: Discussionmentioning
confidence: 99%
“…Poland and colleagues identified heterogeneity in smokers and nonsmokers attitudes to SHS management, distinguishing between the various tolerance levels, interactions, and response styles of smokers and nonsmokers to smoke exposure [53]. Robinson and colleagues discovered a range of implementation styles among participants with home smoking policies in Scotland, including those based on informal discussions, to “negotiated” or “enforced” smoking restrictions [54]. A population based study by Germain and co-authors examined the responses of nonsmokers to smokers and SHS in Australia and found that many nonsmokers were unwilling to confront smokers, despite being bothered by SHS exposure [55].…”
Section: Introductionmentioning
confidence: 99%